A CORRELATION BETWEEN STUDENTS’ LISTENING AND WRITING SKILLS: A STUDY AT AN ISLAMIC BOARDING SCHOOL - Royhan Kamal; Hikmah Pravitasari; Amila Yashila Rahmah; Siti Febriyanti; Isma Ristiyana; Nurul Adhani; Iqbal Rosyid (Journal Fascho in Education Conference-Proceedings, 2021)
The study explored the relationship between listening and writing skills of second-grade junior high school students of an Islamic boarding school in Indonesia. This research aimed at: (1) how is the performance of males and females’ listening and writing skills? (2) how is the portrayal of students' listening skills compared to students' writing skills in Islamic boarding schools? and (3) whether there is a correlation between students' listening skills and students' writing skills in Islamic boarding schools? The data was obtained from listening and writing scores. Results showed that r-count > r-table (r-count= 0.8699; r-table= 0.3291). It can be concluded that the student's performance in the listening and writing scores was statistically significantly correlated. However, the significant correlation of listening and writing skills in this study is feasibly valid for the context.